Barriers of supply chain management practice in manufacturing companies in republic of Yemen: pre-war perspective - Abu Al- Rejal, Hussein Mohammed Esmail; D. Abu Doleh, Jamal; Mohammed Salhieh, Loay; Mohamed Udin, Zulkifli; Mohtar, Shahimi (ExcelingTech Publishers, 2017)
Supply chain management (SCM) is a backbone of manufacturing firms, it enable them to manage all tasks throughout business process. Therefore, investigating the barriers for supply chain management has become significant to assist them for better practicing for SCM. However, the main aim of this paper is to describe the current technology, relationship, and alignment barriers within manufacturing companies in Yemen. A quantitative method was adopted using a questionnaire and a sample of 65 Yemenis respondents who belong to the medium management level of the manufacturing companies in Yemen. Data was analyzed using the SPSS Generally, the findings revealed that Suppliers’ and customer geographical distance from own facilities represent the most barriers to manufacturing companies in adopting SCM in Yemen. Discussions of the findings, implication and limitation of the study were also included.